EFEK PEMBERIAN MULTI MICRO NUTRIENT (MMN) DAN KONSELING GIZI TERHADAP STATUS GIZI WANITA PRAKONSEPSI: Effects Of Giving Multi Micro Nutrients (MMN) And Counseling Nutrition On The Nutritional Status Of Preconception Women - Fandir, Abdul; Dahlia, Besse; Alwi, Juwitriani; Zakiah, Nur (Media Gizi Pangan, 2024)
The preconception period is the time before pregnancy, during which preconception women are assumed to be adult women or women of childbearing age ready to become mothers, where nutritional needs during this period differ from those of children, adolescents, or the elderly. Pre-marital women suffering from undernutrition can lead to anemia, maternal death during childbirth, fetal death, low birth weight babies (LBW), premature birth, birth defects, and infant death. This study aims to examine the relationship between the nutritional status of preconception women and the consumption of Multiple Micronutrient Supplementation (MMN), nutritional counseling involvement, and the frequency of nutritional counseling attendance.The study design is cross-sectional. The population consists of all preconception women who meet the inclusion criteria in the Batui Selatan district. The sampling technique used purposive sampling, and the study was conducted from October to December 2023. Data collection used a questionnaire to determine MMN consumption and involvement in nutritional counseling, nutritional status was assessed by measuring height, weighing, and measuring mid-upper arm circumference. The analysis used univariate and bivariate, using the Chi-Square test. The results showed that there was a significant relationship between the nutritional status of preconception women and the level of MMN consumption (P=0.001), and nutritional status with attendance in nutritional counseling (P=0.005). this it can be concluded that MMN consumption and nutritional counseling affect the nutritional status of preconception women.